Interdisciplinary undergraduate education: water as life, death, and power and the certificate in global health disparities - Dr. Anja Mueller, Phd; Stephen J Juris, PhD; Cathy Willermet, PhD; Eron Drake, EdD; Samik Upadhaya, MS; Pratik Chhetri, BS (Elsevier, 2014)
Background: Central Michigan University's student chapter of Universities Allied for Essential Medicines organised a conference on global health disparities in April, 2011. From this conference came a student-driven initiative to develop interdisciplinary courses on health-related topics, and courses centred on global health and social justice. We describe the preparation and assessment of an interdisciplinary course about water. Methods: The course was cotaught by the anthropology, biology, and chemistry faculty to 28 undergraduate students with anthropology, biology, chemistry, and other majors. The course combined waterborne diseases and water treatment with cultural-related and power-related barriers to clean water. The course included a student-mentored seminar stressing activism on water-related issues. The course's theme examined the effect of cholera, a waterborne disease, in a global context. Findings: Analysis of pre-class and post-class questions about student attitudes via a written questionnaire showed an increase in social awareness and desire to continue to act towards solutions of global problems. For example, of 29 questions concerning civic engagement issues, all 29 responses showed an increase in agreement, with 11 showing statistically significant increases (28 degrees freedom). Assessment of student interdisciplinary thinking showed trends towards an increased ability to solve complex issues with interdisciplinary logic for seven of eight groups of students (the eighth group kept its high level). Interpretation: The student initiative led to the development of an interdisciplinary course that included activism. This course has been expanded to an interdisciplinary undergraduate certificate in global health disparities and might lead to an interdisciplinary major or minor in the future. Funding: Central Michigan University (CMU) Faculty Center for Innovative teaching (FaCIT).